Cultural activity at work: reciprocal associations with depressive symptoms in employees - Theorell, Töres (Int Arch Occup Environ Health, 2019)
PURPOSE: Several studies have shown that cultural activities may promote health. There are also prospective population studies which show that regular participation in cultural activities could reduce morbidity and mortality. To what extent such associations could be applied to the work arena is not so well known, although findings in a few studies support the assumption that cultural activities organized from the work site might improve employee health. An important question discussed in the literature is the extent to which associations between cultural activity at work and employee mental health could be reversed, for instance, with depressive mood resulting in withdrawal from cultural activity at work (backwords) rather than the opposite (forwards). The present study addresses this question. METHODS: Using a biennial national job survey with seven waves (SLOSH), we examined 2-year follow-up periods in 7193 men and 9313 women in the years 2006–2018. The question regarding cultural activity at work was examined prospectively (using multilevel structural equation modelling) both forwards and backwards in relation to a standardized score for depressive mood (SCL-CD(6)) in participants working at least 30% both at start and end of the 2-year period. RESULTS: The analyses were made separately for men and women and with age and education level as confounders. The findings show that there are highly significant prospective relationships for both men and women in both directions concomitantly. CONCLUSIONS: Participation in cultural activity at work may protect employees from worsening depressive feelings, but depressive feelings may also inhibit participation in such activities.